Perspectives on orchid conservation in botanic gardens - Swarts, N.; Dixon, Kingsley (Elsevier, 2009)
Orchids, one of the largest families of flowering plants, face an uncertain future through overexploitation, habitat loss and impacts of climate change. With their intricate abiotic and biotic dependencies, orchids typify the plight of global plant resources and, thus, provide ideal model species for ecological tracking and focussing conservation programs. Botanic gardens worldwide have traditionally been major centres of excellence in orchid horticulture, research and conservation as orchids generate wide public and educational appeal. Here, we highlight the role of botanic gardens in areas key to orchid conservation. With pristine habitats under threat globally, the challenge for orchid conservation programs will ultimately depend upon developing ecological restoration technologies, whereby orchids are reinstated into sustainably restored habitats. Crown Copyright © 2009.